PENERAPAN MODEL PEMBELAJARAN KOOPERATIF QUESTION STUDENT HAVE UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN HIDROLISIS GARAM DI KELAS XI SMAN 1 BUKIT BATU KABUPATEN BENGKALIS - Rina Annisa; Erviyenni Erviyenni; Armiyus Thaib (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract : The purpose of this research is to  increase  student achievement  on the subject of salt hydrolysis in  class XI  SMAN 1 Bukit Batu Kabupaten Bengkalis. Form of research  is  experiment  research  with  pretest-posttest  design.  The sample consisted  of  two  classes.  Experiment  class  was given  implementing  model cooperative  learning Question Student Have, while the  control class was not given  implementing model cooperative  learning Question Student Have. The   t-test  is used for data analysis technique.  Based on the  final  results  of data processing  using  t-test  formula with dk=39  and  ɑ =0,05  obtained  tarithmetic > ttable (2.75 > 1.68)  means that  the application of  model  cooperative learning  Question Student Have can  improve student’s achievement on the subject of salt hydrolysis  in class XI SMAN 1 Bukit Batu Kabupaten Bengkalis. The improvement of student’s achievement in experiment class was supported by N-Gain score 0,74 that included in high category. Key Words :  Question Student Have,  Learning  Achievement,  Salt Hydrolysis